The reliability and validity of the Temporal Focus Scale in young Japanese adults. (1st December 2017) - Chishima, Yuta; McKay, Michael T.; Murakami, Tatsuya
Abstract: Temporal focus is understood as one component of an individual's time perspective, and is defined as the attention individuals devote to thinking about the past, present, and future. The 12-item Temporal Focus Scale is comprised of 3 factors ( past, current, and future focus ). In this study, we examined the reliability and validity of Temporal Focus Scale scores in a sample of 977 young Japanese adults, aged 18–24 years old. The hypothesized 3 factor structure was confirmed, although there were problems with item number 10. Internal consistency estimates for scores without item 10 were over 0.70, and seven-week test-retest reliability was also adequate. To verify the convergent and discriminant validity, we tested the relationship between scores and time perspective, time attitudes, life satisfaction, self-esteem, and career confidence. Results of correlational analyses supported our hypotheses. Specifically, a future focus was more strongly correlated with career efficacy than a past or current focus . Highlights: The 12-item Temporal Focus Scale (TFS) is comprised of 3 factors. The 3 factor structure was confirmed, although there were problems with item 10. Reliability and validity scores without item 10 were adequate. Results of correlational analyses supported study hypotheses. Specifically, a future focus was strongly correlated to career efficacy.